Permission to grieve, please: Exploring the concept of disenfranchised grief - Mouton , Dawid P (Stellenbosch Theological Journal, 2024)
The death of a loved one can be devastating to those who remain behind. The sense of profound loss, pain, emptiness, and disorientation presents significant challenges to those who experience such losses, and even other types of losses. Although grief and mourning are normal responses to this, the process itself may be complex and challenging. This can be particularly true when the grieving process is disrupted, may be regarded as inappropriate, or even worse, when it is not legitimised at all. The article explores some of the dynamics of prolonged or complicated grieving related to the loss of a loved one, with particular focus on the notion of disenfranchised grief. The author argues that ignoring the existence and impact of grief-denying cultures and practices, due to social delegitimization, or other factors, may severely impact a person’s ability to regain a meaningful and balanced life after such loss. In discussing these the article inevitably reflects on the relevance and appropriateness of the notions of disenfranchised grief and prolonged or complicated grief.